Investigating The Relationship Between Core Muscle Strength And Technical Performance In Selected Mat-Based Stability Exercises (Journal of Namibian Studies : History Politics Culture, 2022)
Stable movements are crucial in a range of physical activities such as sports, dancing, and gymnastics. These motions require a significant amount of coordination, balance, and the capacity to retain control over the body's center of mass. The center of mass, located on the body's midline, is a critical factor for stability during these exercises since it represents the point where the body's weight is concentrated. The aim of this study was to investigate if enhancing the power of the core muscles may enhance the proficiency of certain stability exercises done on a mat placed on the floor. The activities included push-ups, abdominal exercises, handstands, headstands, back exercises, and pull-ups. The current review exhibited a significant increase in their technical performance during the stability movements. Based on the findings, focusing on the core muscles during training may improve the precise execution of stability exercises done on a mat or floor.